2022
DOI: 10.1053/j.gastro.2021.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Impairment of Short-Chain Fatty Acid and L-Isoleucine Biosynthesis in Gut Microbiome in Patients With COVID-19

Abstract: Background & Aims SARS-CoV-2 infection is associated with altered gut microbiota composition. Phylogenetic groups of gut bacteria involved in the metabolism of short chain fatty acids were depleted in SARS-CoV-2-infected patients . We aimed to characterize functional profile of gut microbiome in patients with COVID-19 before and after disease resolution. Methods We performed shotgun metagenomic sequencing on fecal samples from 66 antibiotics-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
179
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(224 citation statements)
references
References 48 publications
(52 reference statements)
19
179
0
1
Order By: Relevance
“…3j. In line with a previous study at the metabolic capacity level 39 , these results indicate that the gut microbiome of patients with COVID-19 did not return to a relatively healthy status right after their recovery from SARS-CoV-2 infection. We then observed that disease severity of COVID-19 was significantly positively associated with the gut microbiome dissimilarity between COVID-19 patients and Non-COVID-19 controls (Fig.…”
Section: Alterations Of the Human Microbiome In Covid-19 Patientssupporting
confidence: 91%
See 1 more Smart Citation
“…3j. In line with a previous study at the metabolic capacity level 39 , these results indicate that the gut microbiome of patients with COVID-19 did not return to a relatively healthy status right after their recovery from SARS-CoV-2 infection. We then observed that disease severity of COVID-19 was significantly positively associated with the gut microbiome dissimilarity between COVID-19 patients and Non-COVID-19 controls (Fig.…”
Section: Alterations Of the Human Microbiome In Covid-19 Patientssupporting
confidence: 91%
“…Among the 63 protective nrMAGs, the dominant species were Blautia A obeum (13 nrMAGs), Bariatricus comes (9 nrMAGs), Faecalibacterium prausnitzii D (6 nrMAGs), Blautia A wexlerae (6 nrMAGs), Faecalibacterium sp900539945 (4 nrMAGs), Dorea longicatena B (3 nrMAGs), Blautia A sp003480185 (3 nrMAGs), Blautia A sp003471165 (3 nrMAGs), Dorea formicigenerans (2 nrMAGs), Fusicatenibacter saccharivorans (2 nrMAGs), and GCA-900066135 sp900543575 (2 nrMAGs). Importantly, we found that some of these species were previously reported (including in the original study Yeoh et al) to be decreased in patients with COVID-19 such as Blautia obeum 11,18 , Faecalibacterium prausnitzii 17,18,39,47 , and Dorea formicigenerans 17,18 . Interestingly, those protective nrMAGs also showed a similar abundance distribution between patients with COVID-19 and Non-COVID-19 controls in the study of Zuo et al 17 ( Fig.S9 ).…”
Section: Resultssupporting
confidence: 60%
“…The loss of diversity and immunosupportive Faecalibacterium in patients with BSIs mirrored a similar loss of diversity in the most severely sick mice deliberately infected with SARS-CoV-2, and as observed by other labs and other model systems 4951 . Notably, a recent study reproduced these changes in the microbiome in an antibiotics-naïve cohort 52 , suggesting that the viral infection causes gut dysbiosis, either through gastrointestinal infection 5357 or through a systemic inflammatory response 2, 4 . Furthermore, the pronounced increase in Akkermansiaceae in mice was also observed in our patient samples, and has been reported previously in patients and in K18-hACE2 mice 49, 58 .…”
Section: Main Textmentioning
confidence: 82%
“…For instance, oral microbiomes produce vasoactive and anti-inflammatory nitrite, nitric oxide, and other bioactive nitrogen oxides (Koch et al, 2017;Pignatelli et al, 2020). Moreover, specific microbiota-associated metabolites, such as short-chain fatty acids (SCFAs), have been shown to affect the progression of varied diseases, including respiratory diseases (Hecker et al, 2021;Zhang et al, 2021). Lung microbiota comprise nitrate reducers and SCFAs producers, such as Pseudomonas species and Staphylococcus species, which are linked to protection against respiratory diseases by inhibiting histone deacetylases or binding GPR41, GPR43, and GPR109A to alter chemotaxis and phagocytosis, change cell proliferation, and regulate inflammatory responses (McKenzie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%